Media and Sexual Violence in Islamic Boarding Schools: Sara Mills' Discourse Study on Detik.com News - Alindah, Lutfiyah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This study explores the media's role in shaping public perception of sexual violence in Islamic boarding schools (pesantren) in Indonesia. Using Sara Mills’ discourse analysis, this research examines how the positions of the subject (perpetrator) and object (victim) are constructed in news narratives, with a focus on Detik.com’s reporting. The findings indicate that media narratives significantly influence public attitudes by framing the kyai (Islamic scholar) as a figure of authority within a patriarchal structure, while victims—often students—are placed in a vulnerable position. The study highlights how power dynamics and gender relations affect the reporting of sexual violence, influencing social responses and policy discussions. Furthermore, this research underscores the importance of integrating gender education into the pesantren curriculum to foster awareness and prevent future occurrences. By deconstructing media narratives, this study contributes to a broader understanding of how discourse shapes societal views on sexual violence in religious institutions.